Quand le bar devient miroir des mutations sociales post-coloniales dans Temps de chien de Patrice Nganang - Zango, Achille Carlos (Ponti/Ponts, 2021)
Bars in post African colonies are places where all social mutations can be read. It is more or less what one can discern from the reading of Temps de chien by Patrice Nganang. This novel, having Mboudjak, a dog as narrator, presents an atypical place that is the bar Le Client est Roi, belonging to its master Massa Yo, a former civil servant who has to become barman after the economic crisis. While doing a sociocritical analysis of this bar, it becomes apparent that it textualises certain aspects of the Cameroonian society of 1990s. Le Client est Roi is this multi-dimensional place where men from different social background come for several reasons. Because of its constant position as stage of the new items that also permit to read the whole Cameroonian multilingualism, this place finally becomes a source of inspiration for writers. The bar Le Client est Roi mirrors all social mutations of the post-colonial countries of Africa.